The Tort Caused by the Transmission of Coronavirus Infection (A comparative study) - Al-Jabouri, Salim (Journal of Legal Sciences, 2022)
The Corona pandemic has raised many repercussions on all levels and fields, and several questions have arisen, especially in the legal field, where many responsibilities arise due to the way this pandemic is dealt with, exploited by some, or neglected some obligations imposed to confrontit. Civil responsibility emerges as an important part in the scope of dealing with the effects of the Corona pandemic, as some people deliberately or negligently tend to harm others, which calls for resorting to the provisions of civil responsibility. It seems that the burden of civil responsibility falls not only on individuals, but also on private and public legal persons alike.